Certain peculiarities of the professional pedagogical trend among teachers - Navaitienė, J. (Psichologija, 1988)
The main purpose of the present paper is to reveal some peculiarities of such an important component in the structure of the teacher's personality as its professional-pedagogical trend and to prove the necessity of special directing measures. The experimental study with different methodics on the basis of S. Kregždė's instrumental, theory of professional interests was conducted.
Keywords: Teachers; Professional Pedagogical Trend